The usefulness of ultrasonographic measurement of the laryngeal air column width difference before extubation as a predictor of secondary airway obstruction after extubation in children - Arturo Gerardo Garza Alatorre; Veronica Rodríguez Martínez; Yanyn Ameyaly Cabrera Antonio; Jorge Alejandro Franco Fernández; Alejandra Viridiana Zavala Valdes; Valeria Estefania Velázquez Ramírez; Miguel Emanuel Navarrete Juarez (Wolters Kluwer Medknow Publications, 2023)
Background: Postextubation airway obstruction, also called postextubation stridor, is one of the most frequent complications of orotracheal intubation and the main cause of extubation failure (EF). Several potential predictors of extubation outcomes have been investigated, although their predictive value and clinical usefulness are limited. Laryngeal ultrasound and measurements are new, noninvasive, easily reproducible methods for extubation success. The objective of the study was to determine the usefulness of measuring the laryngeal air column width difference (LACWD) as a predictor of EF. Subjects and Methods: This prospective observational study was conducted from December 2022 to March 2023. Patients older than 30 days and up to 16 years of age admitted to the pediatric intensive care unit (PICU) and intubated with an endotracheal tube with a balloon for >24 h and with their first attempt at extubation were evaluated. The LACWD was measured before extubation. The first measurement was made with the balloon inflated and the second with the balloon deflated, calculating the difference between the two measurements. Results: Forty-five patients were assessed. The median number of days in the PICU was 8 (interquartile range 2-6). We found that the greater the difference in the air column, the lower the risk of EF ([P = 0.418] odds ratio [OR] =0.101 95% confidence interval [CI] =0.000-26.000), and the greater the number of days (>3), the greater the risk of EF ([P = 0.819] OR = 0.996; 85% CI = 0.965-1.028). Conclusions: No statistically significant relationship was found in the LACWD in our patients. We believe that it is important to carry out an extended study, with age group stratification, to assess its use.